PENGEMBANGAN BAHAN AJAR BERBENTUK KOMIK MATEMATIKA BERBASIS ANDROID DENGAN PENDEKATAN RME - M Amirul Latif; Chusnal Ainy; Achmad Hidayatullah (Jurnal Pendidikan Matematika (JPM), 2020)
This research starts from the low activeness and student learning outcomes caused by several factors including conventional mathematics learning where the teacher teaches only with the lecture method and other factors are the factors of teaching material students have less attractive and incomplete so that the learning material cannot be conveyed properly and lack of interest in students reading the material available in teaching materials. This study aims to develop teaching materials in the form of android-based comics with the RME approach to quadrilateral flat material. Comic-shaped teaching materials use a 4-D development model which includes 4 stages, which include the stages of defining, planning, developing and disseminating, in this study limited to the development stage. This type of research is the development of Research & Development (R & D) and uses the 4D development model. The learning outcomes test of students who have carried out learning using an Android-based comic-based teaching material with the RME approach in class VII-B schools in Muhammadiyah Middle School 15 Surabaya obtained completeness of 74.07%. Students' responses to the Android-based comic-based teaching materials developed were obtained at 85.19% which are included in the criteria of "very strong". The results of field trials in class VII-A Muhammadiyah Middle School 15 Surabaya obtained the classical completeness of the learning outcomes test of 88.89%. Student responses to the comic-shaped teaching material developed were obtained by 92.75% which was included in the criteria of "very strong".